A Late Phase of Long-Term Synaptic Depression in Cerebellar Purkinje Cells Requires Activation of MEF2 - Andzelm, Milena M. (Cell Rep, 2019)
The MEF2 family of transcription factors restricts excitatory synapse number in an activity-dependent fashion during development, yet MEF2 has not been implicated in long-term synaptic depression (LTD), which is thought to initiate synapse elimination. Mutations in MEF2 pathways are implicated in autism spectrum disorders, which include cerebellar dysfunction. Here, we test the hypothesis that cerebellar LTD requires postsynaptic activation of MEF2. Knockdown of MEF2D produces suppression of the transcription-dependent late phase of LTD in cultured Purkinje cells. The late phase of LTD is also completely blocked in Purkinje cells derived from MEF2A+MEF2D null mice and rescued with plasmids that drive expression of MEF2D but not phosphatase-resistant mutant MEF2D S444D. Wild-type Purkinje cells transfected with a constitutively active form of MEF2 show no alterations of synaptic strength. Thus, postsynaptic activation of MEF2 by S444 dephosphorylation is necessary, but not sufficient, for the late phase of cerebellar LTD.